Research on the Resonance Suppression Method for Parallel Grid-Connected Inverters Based on Active Impedance - Zhao, Tao; Cao, Yunkai; Zhang, Mingzhou; Wang, Chunlin; Sun, Quan (Frontiers in Energy Research, 2022)
Under the condition of weak grid, the coupling between parallel inverters and grid impedance is easy to cause harmonic resonance, which seriously affects the grid-connected power quality. First, the equivalent circuit model of the multi-inverter parallel system is established, and the mechanism of harmonic resonance is analyzed from the perspective of impedance; through the resonance detection method based on a self-tuning filter, the voltage resonance component of the parallel node is extracted; on that basis, an active impedance is designed to suppress the resonance of the multi-inverter parallel system, which can equivalently construct a virtual impedance branch to improve the grid impedance characteristics at the resonance frequency, and its effectiveness is verified using the impedance stability criterion. Finally, simulation experiments are carried out. The results show that this method can effectively suppress the resonance of the multi-inverter parallel system and can significantly improve the adaptability of inverters to weak grid.